Speeding up lattice QCD simulations with clover-improved Wilson fermions - Hasenbusch, Martin; Jansen, Karl (Nuclear physics. B, Particle physics, 2003)
We apply a recent proposal to speed up the hybrid Monte Carlo simulation of systems with dynamical fermions to two flavour QCD with clover-improvement. The basic idea of our proposal is to split the fermion matrix into two factors with a reduced condition number each. In the effective action, for both factors a pseudo-fermion field is introduced. For our smallest quark masses we see a speed-up of more than a factor of two compared with the standard algorithm.
Gesehen am 05.07.2022